2022
DOI: 10.1097/md.0000000000032006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome and its associated factors among HIV-MTB co-infected patients in Sichuan, China: A retrospective study

Abstract: Human immunodeficiency virus (HIV)-Mycobacterium tuberculosis (MTB) co-infection has become a pressing global public health problem. Although tuberculosis (TB) is both treatable and curable, it has been exacerbated by the HIV/acquired immune deficiency syndrome (AIDS) epidemic. HIV-MTB co-infected patients have a variety of disease-specific, and treatment-related factors that can adversely affect their treatment outcomes. This study was conducted to assess the outcomes of TB treatment and its associated factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…In this study, it was found that men had the highest proportion (84.82%) of TB/HIV coinfection, which is consistent with the findings of other studies [ 15 , [38] , [39] , [40] ]. However, a study conducted in South Africa by Mahtab et al reported that coinfection was more prevalent in women than in men [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, it was found that men had the highest proportion (84.82%) of TB/HIV coinfection, which is consistent with the findings of other studies [ 15 , [38] , [39] , [40] ]. However, a study conducted in South Africa by Mahtab et al reported that coinfection was more prevalent in women than in men [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that patients with SPPTB and coinfection had a higher probability of unsuccessful TB treatment compared to other coinfected patients. However, in contrast to these findings, the study by Yang et al reported a higher probability of unsuccessful TB treatment in HIV coinfection patients with EPTB compared to PTB patients [ 39 ]. It should be noted that in that study, unlike the present study, PTB patients were not analyzed based on smear type.…”
Section: Discussionmentioning
confidence: 90%
“…Tuberculosis and HIV can significantly impact an individual's immune systems by evading immune monitoring functions; however, the exact mechanisms are not completely understood. Mycobacterium tuberculosis and HIV can accelerate immunological impairment and lead to premature death if not treated (Umayorubhagom & Baliga, 2023;Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%